2018
DOI: 10.1080/00365521.2018.1476913
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-145 promotes esophageal cancer cells proliferation and metastasis by targeting SMAD5

Abstract: Our study uncovered the crucial role of miR-145/SMAD5 in esophageal cancer and highlighted its target potential for diagnostic and therapeutic purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…Next, 38 overlapping genes were selected through intersecting the predicted target genes scoring over 75 in the miRDB database, scoring over 0.85 in the mirDIP database and the top 50% in the other databases (Figure 1G). Furthermore, it has been previously reported that the SMAD5 gene plays an important regulatory role in a variety of tumors (15,16). The KEGG database indicates that SMAD5 is closely associated with the TGF-β signaling pathway (map04350), which is considered to be one of the key pathways in the regulation of NPC progression (17)(18)(19).…”
Section: Resultsmentioning
confidence: 99%
“…Next, 38 overlapping genes were selected through intersecting the predicted target genes scoring over 75 in the miRDB database, scoring over 0.85 in the mirDIP database and the top 50% in the other databases (Figure 1G). Furthermore, it has been previously reported that the SMAD5 gene plays an important regulatory role in a variety of tumors (15,16). The KEGG database indicates that SMAD5 is closely associated with the TGF-β signaling pathway (map04350), which is considered to be one of the key pathways in the regulation of NPC progression (17)(18)(19).…”
Section: Resultsmentioning
confidence: 99%
“…miR‐145 is a newly discovered miRNA, which is significantly less expressed in breast cancer (Ding et al, ), cervical cancer (Sathyanarayanan et al, ), glioma (Xu et al, ), colon cancer (Li et al, ), esophageal cancer (Zhang et al, ), and non‐small‐cell lung cancer (Yin et al, ). The genes regulated by miRNA‐145 are different in different tumors, and the molecular mechanisms of their anti‐cancer effects are also different.…”
Section: Discussionmentioning
confidence: 99%
“…[ 38 ] For SMAD5, it has been reported that miR-145 can promote the migration and migration of esophageal cancer cells by inhibiting theexpression of SMAD5. [ 39 ] Fstl1 can promote glioma growth through SMAD1/SMAD5/SMAD8. [ 40 ] At the same time, SMAD5 expression increases in prostate cancer, which is closely related to postoperative survival.…”
Section: Discussionmentioning
confidence: 99%